(untitled) - FAO (Rome, 1988)
The FAO Yearbook of Forest Products is a compitation of annual statistical data on production and foreign trade of forest commodities for all countries and territories of the world. It includes tables showing direction of trade and average unit values of trade for certain products. Statistical information in the Yearbook is based on data provided to the FAO Forestry Department by the countires through questionnairies or Official publications.
Keywords: forests and forestry